Level of Knowledge and Practices of Neonatal Ecology in the Nursing staff of a Hird Level Health Institution - Quintero Ramírez, Nini Milena
Introduction: Preterm or high-risk newborns require highly complex treatments and interventions provided in the neonatal intensive care unit where their stay is prolonged and they are exposed to both physical and environmental cruel measures: noise, light and positioning, which can in an unfavorable way in their health, clinical evolution and prognosis.   If the nursing team has knowledge and practices that minimize such aggressions, the quality of life of neonates is improved. Objective: to determine the knowledge and practices on neonatal ecology in the nursing staff of a health institution. Methodology: Quantitative, observational, descriptive, cross-sectional, descriptive study in which two instruments were applied: a checklist to verify the practices of the nursing staff; and a questionnaire that inquired about their knowledge of neonatal ecology. Statistical analysis was performed with SPSS version 29. Results: It was determined that 27 of the nurses have a certain level of knowledge and skills on neonatal ecology; 77.14% obtained a regular qualification in the practices for newborn care with 33.93%, 94% were female, and were between 45 and 54 years of age, 23% were professionals and 77% were technicians assisting the neonate. Conclusion: knowledge is regular, in the same way the practices on Neonatal Ecology in the nursing staff present a regular balance, in relevant distinctions such as non-pharmacological measures for the management of stress, pain, as well as the exposure to noise above the allowed levels, not covering the patient's ears of objects that alter their auditory development. Intervening in the evolution of their neurodevelopment. Therefore, it can be inferred that the nursing staff has some degree of knowledge of neonatal ecology, but at the same time they do not apply it.